2008
DOI: 10.1073/pnas.0801609105
|View full text |Cite
|
Sign up to set email alerts
|

Peptide antisense nanoparticles

Abstract: We have designed a heterofunctionalized nanoparticle conjugate consisting of a 13-nm gold nanoparticle (Au NP) containing both antisense oligonucleotides and synthetic peptides. The synthesis of this conjugate is accomplished by mixing thiolated oligonucleotides and cysteine-terminated peptides with gold nanoparticles in the presence of salt, which screens interactions between biomolecules, yielding a densely functionalized nanomaterial. By controlling the stoichiometry of the components in solution, we can co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
78
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 59 publications
1
78
0
2
Order By: Relevance
“…Contrastingly, MEFs treated with Sticky-flares targeting U1 snRNA distinctly showed internuclear fluorescence. Importantly, SNA constructs are sequestered to the cytosol of live cells and cannot enter the nucleus on their own (33). Thus, the internuclear fluorescence of U1 Sticky-flares indicates specific release from the nanoparticle surface and subsequent transport of the fluorescentlabeled RNA target into the nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…Contrastingly, MEFs treated with Sticky-flares targeting U1 snRNA distinctly showed internuclear fluorescence. Importantly, SNA constructs are sequestered to the cytosol of live cells and cannot enter the nucleus on their own (33). Thus, the internuclear fluorescence of U1 Sticky-flares indicates specific release from the nanoparticle surface and subsequent transport of the fluorescentlabeled RNA target into the nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…The details of this preparation are described elsewhere (Jeynes et al, 2013a), where we also show that the TAT coating compared to a FBS coating, increases the number of GNPs in the cell by about 5 times. Of note, it has been shown that coating the GNPs with bovine serum increases the diameter of the GNP by about 10nm (Tsai et al, 2011), while coating with TAT increases it by about 30nm (Patel et al, 2008).…”
Section: Gold Nanoparticle Treatmentmentioning
confidence: 99%
“…Building on their previous work with proteins facilitating intracellular trafficking, the peptides bound to the nanoparticles were linked to increased cellular uptake and/or altered intracellular localization. The peptideoligonucleotide-modified nanoparticles showed a 75% decreased expression of glyceraldehyde 3-phosphate dehydrogenase, whereas oligonucleotide-modified nanoparticles showed only a 50% decrease in expression (4 ). Interestingly, the increased knockdown was not associated with greater numbers of nanoparticles per cell, but the nanoparticles were reproducibly associated more closely to the cell's nucleus.…”
Section: Peptide Antisense Nanoparticlesmentioning
confidence: 79%
“…It is against this backdrop that a series of papers out of the Mirkin group at Northwestern University is significant (1)(2)(3)(4). Few disagree with the power that oligonucleotide probes offer as detectors of nucleic acids and regulators of gene expression in living cells.…”
mentioning
confidence: 99%